Townsend Discharge and Streamer Breakdown within Sphere-Air-Sphere Configuration - Khalaf, Thamir H.; Ghayb, Dawser Hussain (Iraqi Journal of Science, 2023)
The main aim of the present paper is to study the electric breakdown in a uniform electric discharge system. The system consists of two spheres separated by a dielectric. The dielectric is dry air. Certain boundary conditions are taken into consideration as applied voltage, pressure, and domain. The formation of discharge types as Townsend and streamer under different distance gaps (1, 0.9,0.8, 0.6, 0.4, 0.2, 0.1) mm was sudied. The temperature effect on the breakdown voltages for the discharge process is also included. Seven different temperature steps are chosen in the study.  Comsol Multiphysics software is used for the simulation model as a plasma model. Results show that as the gap distance increases the breakdown voltage increases for each of the discharges. For maximum electric field, as the distance increases the field also increases. For gap distance, the temperature effects are more apparent at the higher values of the pressure.  The maximum electric field increases as the voltage increases with the temperature.